Modern radiation-hygienic state of the territories of the Globus-4 and Gorizont-1 peaceful nuclear explosions in the Komi Republic - A. M. Biblin; K. V. Varfolomeeva; K. A. Sednev; S. A. Ivanov; V. S. Repin; A. G. Georgieva (Радиационная гигиена)
The article presents results of a study of the radiation environment on territories adjacent to the sites of the “Globus-4” and “Gorizont-1” peaceful nuclear explosions in the Komi Republic. Field survey was carried out in July 2021. The work provides an assessment of the radiation situation in terms of the main indicators: ambient dose equivalent rate, the content of anthropogenic radionuclides in soil, tritium in the water of water bodies and drinking water supply sources in the settlements nearest to the sites of the peaceful nuclear explosions. The values of gamma radiation ambient dose equivalent rate in all the surveyed territories are at the level of fluctuations of natural regional radiation background and amounted to 0.03 – 0.07 µSv/h in the territory of peaceful nuclear explosion “Globus-4”, 0.01 – 0.05 µSv/h in the territory of “Gorizont-1”. No contaminated soil areas with anthropogenicradionuclides were detected. Tritium activity concentration in water samples does not exceed 5 Bq/kg, which is typical for global levels of this radionuclide in water bodies. The study has shown that the radiation situation in the territory of peaceful nuclear explosions “Globus-4” and “Gorizont-1” meets the requirements of SanPiN 2.6.1.2819-10 “Ensuring radiation safety of the population living in the areas of (1965 – 1988) nuclear explosions for peaceful aims” and currently poses no threat to public health. A conservative dose estimate of additional anthropogenic exposure of individuals from the population from tritium intake with water from centralised water supply sources was 0.065 µSv/year. Longterm radiation safety of the researched territories requires organisation of radiation monitoring, determination of protected zone boundaries and installation of readable information signs warning about radiation hazard and prohibition of economic activities.